DOI: 10.3990/1.9789036531320
|View full text |Cite
|
Sign up to set email alerts
|

Photon imaging using post-processed CMOS chips

Abstract: e cover shows images of UV light recorded with a Timepix chip (chapter 5). To do this an InGrid detector structure and a CsI photocathode have been postprocessed onto the IC. e background that is used on the cover is an image of patterns in porous alumina, a material that has been investigated for the structures described in chapter 6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 112 publications
(162 reference statements)
0
1
0
Order By: Relevance
“…Other feasibility studies demonstrated the possibility to measure photon polarisation [109], the general capabilities to detect photons [110] and the application in tumour proton therapy [111]. To summarise, the InGrid device is used for a wide variety of utilisations not only in the field of particle physics.…”
Section: Applicationsmentioning
confidence: 99%
“…Other feasibility studies demonstrated the possibility to measure photon polarisation [109], the general capabilities to detect photons [110] and the application in tumour proton therapy [111]. To summarise, the InGrid device is used for a wide variety of utilisations not only in the field of particle physics.…”
Section: Applicationsmentioning
confidence: 99%